Reducing Chronic Visuo-Spatial Neglect Following Right Hemisphere Stroke Through Instrument Playing - Bodak, Rebeka; Malhotra, Paresh; Bernardi, Nicolò F.; Cocchini, Gianna; Stewart, Lauren (Frontiers in Human Neuroscience, 2014)
Unilateral visuo-spatial neglect is a neuropsychological syndrome commonly resulting from right hemisphere strokes at the temporo-parietal junction of the infero-posterior parietal cortex. Neglect is characterised by reduced awareness of stimuli presented on patients’ contralesional side of space and has previously been shown to be improved by a number of motivational influences, including listening to preferred music and numerical sequence completion. Here we examined whether playing musical sequences on chime bars – an instrument with a horizontal alignment – would bring about clinically significant improvement in chronic neglect. Two left neglect patients completed an intervention comprising four weekly 30-minute music sessions involving playing scales and familiar melodies on chime bars from right to left. Two cancellation tests (Mesulam shape, BIT star), the line bisection test, and the neglect subtest from the computerised TAP (Test for Attentional Performance) battery were administered three times during a preliminary baseline phase, before and after each music session during the rehabilitation phase to investigate short-term effects, as well as one week after the last intervention session to investigate whether any effects would persist. Both patients demonstrated significant short-term and longer-lasting improvements on the Mesulam shape cancellation test. One patient also showed longer-lasting effects on the BIT star cancellation test and scored in the normal range one week after the intervention. These findings provide preliminary evidence that active music-making may help neglect patients attend more to their affected side.